2006
DOI: 10.1111/j.1464-410x.2006.06013.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of serum testosterone after neoadjuvant androgen deprivation therapy and radical radiotherapy in localized prostate cancer

Abstract: before treatment (baseline), during LHRHa treatment, and at 6, 12, 18, 24 and > 40 weeks after the last LHRHa injection. RESULTSThe median (range) time from the first to last LHRHa injection was 116 (54-194) days. The mean (95% confidence interval) testosterone levels (in nmol/L) at baseline, during treatment and at 6, 12, 18, 24 and > 40 weeks afterward were 12.0 (10.8-13.1), 0.6 (0.5-0.7), 1.4 (0.6-2.2), 11.4 (9.7-13), 12.2 (10.5-14), 10.4 (8.9-12) and 11.7 (10.5-13). Four men had low baseline testosterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
4
34
0
2
Order By: Relevance
“…In a randomized clinical trial using intermittent hormonal therapy for PCa patients with increasing PSA after definitive local treatment, Gulley et al 6 found that after 6 months of ADT, more than 90% patients achieved supracastrate serum testosterone level by 18 weeks. In another study Murthy and colleagues 8 found that after short-course (lasted 54-194 days) neoadjuvant ADT and radical radiotherapy in localized PCa, all patients recovered to supracastrate testosterone level by 12 weeks after the last LHRH agonists injection. Results from the present study showed that 97.9% and 100% patients could recover to supracastrate testosterone level at 3 and 6 months after cessation of 9-month ADT.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a randomized clinical trial using intermittent hormonal therapy for PCa patients with increasing PSA after definitive local treatment, Gulley et al 6 found that after 6 months of ADT, more than 90% patients achieved supracastrate serum testosterone level by 18 weeks. In another study Murthy and colleagues 8 found that after short-course (lasted 54-194 days) neoadjuvant ADT and radical radiotherapy in localized PCa, all patients recovered to supracastrate testosterone level by 12 weeks after the last LHRH agonists injection. Results from the present study showed that 97.9% and 100% patients could recover to supracastrate testosterone level at 3 and 6 months after cessation of 9-month ADT.…”
Section: Discussionmentioning
confidence: 95%
“…[3][4][5][6][7][8][9] It has been reported that if a patient had baseline testosterone level below the normal range, it is difficult for him to recover to normal range after the cessation of ADT. 4 The first strength of the present study is that we defined a serum testosterone level o230 ng dl 21 as normal and excluded patients whose baseline testosterone lower than normal level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations